Analysis of the Influence of Fraud Risk Factors According to Fraud Diamond on Fraud Financial Statements in Manufacturing Companies Listed on the Indonesia Stock Exchange - Rossy Pratiwy Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine the influence of external pressure, financial target, ineffective monitoring, rationalization, and capability on financial statement fraud. Financial Statement Fraud is measured by earnings management using discretionary accruals. This study uses secondary data were taken from the manufacturing companies which are listed in Indonesian Stock Exchange. Sample selection is done by purposive sampling method and sample obtained from this research were 45 of a total 135 companies. Method of analysis used multiple linear regression analysis. The result show that simultanoeusly of external pressure, financial target, ineffective monitoring, rationalization, and capability have a significant influence on financial statement fraud. Partially, external pressure, financial target, rationalization, and have no significant influence on financial statement fraud. Ineffective monitoring partially has a significant influence on financial statement fraud.